2019
DOI: 10.1136/bmjopen-2019-030209
|View full text |Cite
|
Sign up to set email alerts
|

Doctor, how can we help you? Qualitative interview study to identify key interventions to target burnout in hospital doctors

Abstract: ObjectiveTo identify priority interventions for the prevention and reduction of work stress and burnout in hospital doctors through analysis of (1) doctors’ experiences of work stress and burnout and (2) their preferences with respect to interventions.DesignQualitative design using semistructured interviews analysed with deductive thematic analysis.SettingHospitals in Ireland.Participants32 hospital doctors (16 practising consultants and 16 doctors in training) from a range of specialties, career stages, hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 50 publications
1
35
1
Order By: Relevance
“…Although 15% indicated that their staffing levels were at or above 75% recommended levels, most (n = 22, 50%) had services operating at 50% staffing levels, with one service having only 20% of recommended resources. However, unlike in other studies, respondents operating with lower than recommended resourcing levels did not report higher BO levels 28. Certain perceptions rather than resourcing were associated with higher BO levels.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…Although 15% indicated that their staffing levels were at or above 75% recommended levels, most (n = 22, 50%) had services operating at 50% staffing levels, with one service having only 20% of recommended resources. However, unlike in other studies, respondents operating with lower than recommended resourcing levels did not report higher BO levels 28. Certain perceptions rather than resourcing were associated with higher BO levels.…”
Section: Discussioncontrasting
confidence: 92%
“…The Medical Council of Ireland Intelligence Report and the Royal College of Surgeons Ireland (RCSI) Health Workforce examined reasons for emigration among Irish medical graduates in 2015. They identified ‘push’ factors to include ‘stressful conditions’ compounded by low staffing and ‘lack of designated and supervised training’,36 37 findings which have been echoed in other studies 12 28. If clinical standards are to remain high, and children and families are to receive expert quality care, then urgent attention needs to be given to both work conditions and physicians’ mental health.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations